Copper‐64‐Alloyed Gold Nanoparticles for Cancer Imaging: Improved Radiolabel Stability and Diagnostic Accuracy1. Issue 1 (24th November 2013) - Zhao, Yongfeng; Sultan, Deborah; Detering, Lisa; Cho, Sangho; Sun, Guorong; Pierce, Richard; Wooley, Karen L.; Liu, Yongjian
Abstract Gold nanoparticles, especially positron‐emitter‐ labeled gold nanostructures, have gained steadily increasing attention in biomedical applications. Of the radionuclides used for nanoparticle positron emission tomography imaging, radiometals such as 64Cu have been widely employed. Currently, radiolabeling through macrocyclic chelators is the most commonly used strategy. However, the radiolabel stability may be a limiting factor for further translational research. We report the integration of 64Cu into the structures of gold nanoparticles. With this approach, the specific radioactivity of the alloyed gold nanoparticles could be freely and precisely controlled by the addition of the precursor 64CuCl2 to afford sensitive detection. The direct incorporation of 64Cu into the lattice of the gold nanoparticle structure ensured the radiolabel stability for accurate localization in vivo. The superior pharmacokinetic and positron emission tomography imaging capabilities demonstrate high passive tumor targeting and contrast ratios in a mouse breast cancer model, as well as the great potential of this unique alloyed nanostructure for preclinical and translational imaging.